Autism and Pervasive Developmental Disorders - Volkmar, Fred R. (Cambridge University Press, 2019)
Interest in autism and related disorders has exploded. Established as an essential book on this complex syndrome, the new edition has been extensively revised to reflect significant advances in research. Featuring contributions from leading international authorities in the clinical and social sciences, the book covers recent progress in our understanding of the field and offers a perspective on the present state of the discipline. With new material on topics such as evidence-based treatment and practice, the book covers changes in diagnosis resulting from the publication of DSM-V, and developments in how autism is understood, including the removal of language delay as a necessary diagnostic criterion. Far-reaching, the book considers aspects from epidemiology, genetics, and neurobiology, to core symptoms, early interventions, and pharmacology. One section critically surveys the history of autism as a diagnostic concept, and issues such as an ageing population and the impact of research on national policy are considered.
Keywords: dept.sed

Reading comprehension strategies in autism spectrum disorders - Bean, Kimberly (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.sed

The need for caregiver support for families of children with ASD - Bean, Kimberly; Meers, K (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.sed

Transition issues and challenges for youth with autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L. J.; Hart, Logan (Pediatric Annals, 2017)
49 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Preface: Special Issue—College Experiences for Students with Autism Spectrum Disorder - Jackson, Scott L. J.; Hart, Logan; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

Brief report: Self-reported academic, social, and mental health experiences of post-secondary students with autism spectrum disorder - Jackson, Scott L. J.; Hart, Logan; Brown, Jane Thierfeld; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
104 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Brief Report: Bullying and Anxiety in High-Functioning Adolescents with ASD - van Schalkwyk, Gerrit; Smith, Isaac C.; Silverman, Wendy K.; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Youth with ASD are more likely to experience bullying than their typically developing peers. This risk has not been studied in youth with ASD transitioning to college. We examined the occurrence of bullying in 35 high functioning youth with ASD who were preparing to attend college. We also examined youth anxiety and ASD symptoms. Fifty-one percent of the sample reported being recent victims of bullying; 31% of parents reported their child was a victim of bullying. Parent report of bullying correlated significantly with ratings of youth social anxiety symptoms. These findings suggest that bullying is an issue of concern for higher functioning, older adolescents with ASD, and that their own reports may be particularly important in identifying its occurrence.
Keywords: Anxiety; Autism spectrum disorder; Bullying; Postsecondary education; dept.sed

Practicing Evidence-Based Practices - Eren, Ruth Blennerhassett; Brucker, Pamela Owen (Evidence-Based Practices and Treatments for Children with Autism, 2011)
Public education in the United States has a history of local control in the development of curriculum and instruction. Although notable court decisions have led to more universal applications of educational policy and practices (Brown v. Board of Education 1954, Oberti v. Clementon 1993), it has been federal law that has resulted in significant changes in instruction. The Individuals with Disabilities Education Improvement Act (IDEA; Public Law 108–142), first enacted in Public Law 94–142, guaranteed the right of a free, appropriate public education for all children, regardless of the severity of their disability. The word “appropriate” resulted in the beginning of what we refer to today as differentiated instruction: instructional strategies that allow a child to learn and progress in an educational setting. The federal law, No Child Left Behind (NCLB; Public Law 107-110), enacted in 2001, contributed to this initiative and added a caveat that these differentiated instructional strategies needed to be grounded in scientifically based research. Indeed, the term “scientifically based research” has been noted to appear in NCLB 111 times (Deshler 2002). The federal government, in IDEA 2004, identified 13 eligibility categories. In order to receive special education services, a student must, through a multidisciplinary evaluation, meet the eligibility criteria established for one of the 13 categories. Since 1975, when PL94–142 was enacted, educational interventions for students receiving special education have expanded, particularly in disability categories with a high level of incidence such as speech and language disorders and learning disabilities. Low-incidence disabilities, such as mental retardation, visual impairments, and autism, have received less attention.
Citation Key Alias: lens.org/104-519-704-094-108
Keywords: General Education; Individualize Education Program; Special Education; Special Education Teacher; Team Meeting; dept.sed